Perancangan Ulang Tata Letak Fasilitas Pabrik PD Ayam Ras dengan Metode Systematic Layout Planning (SLP) - Ade Yulia (Universitas Katolik Parahyangan, 2022)
PD Ayam Ras is a food industry that processes coffee beans into ground coffee ready for brewing. The problems that arise in PD Ayam Ras are caused by unplanned layout design between departments, inefficient material transfer distances and costs material handling that have not been calculated. This causes departments that have closely related material flow sequences to be located far apart. In addition, there is backflow (backtracking) resulting in movement back and forth in the production process. PD Ayam Ras still has empty space that has not been utilized so that space utilization is not optimal resulting in inefficient material flow in the coffee powder production process, thus increasing distance and costs material handling. The purpose of this research was to determine the initial layout of the PD Ayam Ras, analyze the layout of PD Ayam Ras factory based on material handling distances, material handling costs and inter-departmental linkages and produce a proposed layout design for PD Ayam Ras .The method used to redesign the facility layout in PD Ayam Ras factory is Systematic Layout Planning (SLP ) method with the help of Blocplan software. The results of the study obtained an efficiency of 36.02 % with costs material handling of Rp. 540,559.40 per day.